First-year Class Instills Confidence in Nontechnical Skills for Collegiate Success - Anna Levina; Katy Guthrie; Leah Cook; Marvin Pritts (HortTechnology)
Universities are encouraging academic units to offer introductory courses that include content to help new students adapt and adjust to college life, deal with stress, and plan for future careers. Few studies have identified the level of confidence that students have in these skills when they matriculate or after completing such courses. For 3 years, first-year plant science majors were surveyed at the beginning and end of their first semester at Cornell to determine whether a class focused on improving skills for success (PLSCI 1101: Pathways to Success in Plant Sciences) resulted in enhanced confidence. Skills and practices deemed important for success and targeted in class included study habits, constructing a resume, interviewing effectively, developing cultural humility, discovering one’s identity, managing mental health, approaching faculty, exploring graduate school, and learning about plant science careers. Assessing these skills with standard fact-based testing methods is not effective, so we assessed change in confidence during the semester, allowing students to self-assess their own learning. We also were able to examine differences in responses based on gender and matriculation status (freshmen admits vs. transfers) and found that differences were minor across years. The course was most effective at enhancing confidence in knowing about graduate school, learning about faculty interests, writing a resume, and learning about career options. Students entering the class already had a high level of confidence in their ability to manage stress, interview well, talk with faculty, ask questions in class, and study. However, confidence always improved by every measure from the beginning to the end of the semester, and many of these changes were statistically significant. This class succeeded in building confidence in specific skills and practices necessary for a successful college career and future employment.